Konstruksi Sosial Masyarakat terhadap Pemandu Karaoke: Studi Kasus di Desa Botorejo Kecamatan Wonosalam Kabupaten Demak - Sari, Dewi Ratna; Prasetyo, Kuncoro Bayu (JSW: Jurnal Sosiologi Walisongo, 2017)
Karaoke houses that many found in urban areas, nowadays also find into rural areas. The existence of karaoke houses can not be separated from the profession of "karaoke guide", and they often get bad stigma by the public. This study aims to: (1) find out how social construction Botorejo people against karaoke guides; (2) to know the background of the formation of social construction of the community towards karaoke guides, and (3) to know the impact of the social construction on the social relation between the karaoke guide and Botorejo people. This research uses qualitative method with case study approach. Location in Botorejo Village, Wonosalam District, Demak Regency. The data gets from karaoke guides, visitors karaoke houses, managers karaoke houses and people who live in Botorejo Village. The results of the study found that the Karaoke Guides constructed by Botorejo people as âbad womenâ, the background of the socialconstruction of the Botorejo people is due to the daily habits of karaoke guides and because of the medias reference to the existence of karaoke guides. The impact of social construction on social relations between people with karaoke guides is a latent conflict, social careless relation, and apriori images by the Botorejo people.Â